Nilai-Nilai Pendidikan Islam Dalam Tradisi Mandi Berarak Balimau Kasai Di Dusun Simpang Baru Desa Teluk Latak Kabupaten Bengkalis Provinsi Riau - Adha, Ayuni; Yulianti , Eka; Susila, Susila (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
The research method used is a qualitative method with observation and interview techniques with selected informants with purposive sample. The results of the study show that bathing in the Balimau Kasai procession is a tradition that is still highly maintained by the local community to this day as a form of gratitude to Allah SWT and a sense of joy because the holy month of Ramadhan has come and as a symbol of self-purification both physically and mentally ahead of the fasting month of Ramadhan. The traditional procedure for bathing in the Balimau Kasai procession includes parades, distributing cakes and water, bathing in the Balimau Kasai parade, and eating together. Bathing is carried out by several community leaders, religious leaders, and government agencies using water that has been mixed with lime. Bathing in Balimau Kasai hamlet of Simpang Baru Teluk Latak village has social, religious and cultural values for the local community